Conceptualisation and operationalisation of happiness in Islam : a Qur'anic perspective - Alseheel, Ali Youssef (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
What constitutes happiness in Islam, and thus how to measure Muslims' happiness derived from its indigenous meaning, were the questions this study aimed to answer. The study attempted to fill this gap of research by providing a conceptual and operational definitions drawing on the authoritative reference for Muslims; the Holy Qur'an. Hence, a 153-item psychological Measure of Qur'anic-based Happiness (MQBH) was eventually developed, through four stages: (a) Domains and their related attributes of the Qur'an relevant to the notion of human happiness or well-being were identified, through systematic qualitative analyses of the verses of the Qur'an and their scholarly exegeses addressing this concept. The delineated domains constituted the foundation of the derived conceptual definition of happiness in the Qur'an. Consequently, to provide an operational definition (b) an initial set of items was generated, drawing on the identified Qur'anic domains and their attributes; (c) the initial measure was pilot tested with 260 Muslim students of the International Islamic University of Malaysia (IIUM); and then (d) a revised version of the measure was further tested with 745 Muslim students from the same university. Desirable psychometric qualities of the final measure were established, as follows. An exploratory factor analysis yielded five distinct, highly reliable factors: “Qur'anic-Based Spiritual Pursuits, Attainments, & Allah-Consciousness”, “Qur'anic-Based Beliefs & Spiritual Experiences”, “Qur'anic-Based Religious Struggles”, “Qur'anic-Based Positive Emotions”, and “Qur'anic-Based Negative Emotions”. All the subscales of the MQBH demonstrated construct, discernment, criterion, convergent, and incremental validity. The findings indicate that Islam is central to Muslims' happiness, and both conceptualisation and operationalisation, as well as the resultant MQBH, provide scientific, indigenous-based, and multidimensional understanding of happiness in Islam needed to advance the nearly nonexistent psychological theory, practice, and research focused on Muslim populations.